PELAKSANAAN PELATIHAN DAN PENGEMBANGAN PADA PUSAT PELATIHAN PERTANIAN PEDESAAN SWADAYA (P4S) KARYA NYATA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Ahmad Akbar; Zaili Rusli. SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Training and development is an activity to improve the quality of human resources in achieving mastery of skills, knowledge, and abilities. The formulation of the problem in this research is how the